“MY FIRST SEXUAL KNOWLEDGE” VIDEO-ANIMATION-BASED FOR THE PROTECTION OF CHILDREN AGED 4-6 YEARS FROM SEXUAL VIOLENCE - Siti Zuhriyah; Susianty Selaras Ndari (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
The purpose of this research is to develop media “my first sexual knowledge